Return of the lysergamides. Part IV: Analytical and pharmacological characterization of lysergic acid morpholide (LSM‐775). Issue 2 (27th July 2017) - Brandt, Simon D.; Kavanagh, Pierce V.; Twamley, Brendan; Westphal, Folker; Elliott, Simon P.; Wallach, Jason; Stratford, Alexander; Klein, Landon M.; McCorvy, John D.; Nichols, David E.; Halberstadt, Adam L.
Abstract : Lysergic acid diethylamide (LSD) is perhaps one of the best‐known psychoactive substances and many structural modifications of this prototypical lysergamide have been investigated. Several lysergamides were recently encountered as 'research chemicals' or new psychoactive substances (NPS). Although lysergic acid morpholide (LSM‐775) appeared on the NPS market in 2013, there is disagreement in the literature regarding the potency and psychoactive properties of LSM‐775 in humans. The present investigation attempts to address the gap of information that exists regarding the analytical profile and pharmacological effects of LSM‐775. A powdered sample of LSM‐775 was characterized by X‐ray crystallography, nuclear magnetic resonance spectroscopy (NMR), gas chromatography mass spectrometry (GC–MS), high mass accuracy electrospray MS/MS, high performance liquid chromatography (HPLC) diode array detection, HPLC quadrupole MS, and GC solid‐state infrared analysis. Screening for receptor affinity and functional efficacy revealed that LSM‐775 acts as a nonselective agonist at 5‐HT1A and 5‐HT2A receptors. Head twitch studies were conducted in C57BL/6J mice to determine whether LSM‐775 activates 5‐HT2A receptors and produces hallucinogen‐like effects in vivo . LSM‐775 did not induce the head twitch response unless 5‐HT1A receptors were blocked by pretreatment with the antagonist WAY‐100, 635 (1 mg/kg, subcutaneous). These findings suggest that 5‐HT1A activation by LSM‐775 masks its ability to induce the head twitch response, which is potentially consistent with reports in the literature indicating that LSM‐775 is only capable of producing weak LSD‐like effects in humans. Abstract : Lysergic acid morpholide (LSM‐775) appeared as a research chemical in 2013. An extensive analytical characterization is presented followed by pharmacological investigations. LSM‐775 acted as an agonist at the 5‐HT1A receptor and all three 5‐HT2 receptor subtypes. However, the head twitch response was not induced in C57BL/6J mice unless 5‐HT1A receptors were blocked by pretreatment with the antagonist WAY‐100, 635. These findings are potentially consistent with reports indicating that LSM‐775 might only be capable of producing weak LSD‐like effects in humans.